Effect of Profitability, Liquidity and Earning Management on Stock Return in IDX Companies - Mayliza, Riri; Putra, Waldino (UPI YPTK Journal of Business and Economics, 2024)
This study aims to determine whether profitability, liquidity and earnings management can be used to predict the stock return of manufacturing companies listed in Indonesia Stock Exchange. Samples were obtaines randomly on companies listed in Indonesia Stock Exchange as many as 100 companies with over 5-year study period from 2018 to 2022 year. The data used are secondary data from financial statements or annual reports from 2014 to 2018 year. The results showed that the profitability is partially a significant negative effect on Return Shares. Liquidity partially no significant effect on stock returns. Earnings management partially no significant effect on stock returns. and leverage no significant effect on stock returns. Profitability, liquidity, earnings management, and leverage simultaneously have a significant effect on stock returns.